Fluorescent‐tagged Antiscalants: A New Look at the Scale Inhibition Mechanism and Antiscalant Selection. Issue 2 (6th December 2021) - Tkachenko, Sergey; Ryabova, Anastasia; Oshchepkov, Maxim; Popov, Konstantin
Abstract: Solid deposits onto equipment surfaces represent a serious problem all over the world. Mitigation of this process is provided by chemical inhibitors. However, irrespective of successful antiscalant application, the mechanisms of scale inhibition are still not very clear. Thus, the present review summarizes recent advances in novel fluorescent‐tagged antiscalants (polyacarboxylates, phosphonates) application for scale inhibition mechanisms study. Some paradoxical effects, detected during gypsum and barite scale formation visualization are described and interpreted within the "nanodust" concept. It is demonstrated, that the solid nanoimpurities, naturally occurring in both industrial and deionized water samples, are definitely playing a key role in any crystal nucleation process. Such nanoimpurities are responsible for the bulk heterogeneous nucleation in a supersaturated salt solution. Scale inhibitor molecules block and isolate exactly these "nanodust" nucleation centers and therefore retards crystallization process on the whole. The advantages of fluorescent antiscalants to provide a new look at scale inhibition phenomenon and inhibition mechanisms are discussed. Among these, there is a possibility to distinguish particular scale inhibitors in their blends, and an opportunity to track an antiscalant location along the process of scale formation and deposition. Besides, a need of antiscalants testament procedure unification is considered, and a possible role of fluorescent reagents in such a procedure elaboration is indicated. Abstract : The unique advantages of fluorescent antiscalants to provide a new look at scale inhibition phenomenon and inhibition mechanisms are discussed. Among these, there is a possibility to distinguish particular scale inhibitors in their blends, and an opportunity to track an antiscalant location along the process of scale formation and deposition.